Teaching electronic music – journeys through a changing landscape - Emmerson, Simon (Revista Vórtex, 2020)
In this essay, electronic music composer Simon Emmerson examines the development of electronic music in the UK through his own experience as composer and teacher. Based on his lifetime experiences, Emmerson talks about the changing landscape of teaching electronic music composition: "˜learning by doing' as a fundamental approach for a composer to find their own expressive voice; the importance of past technologies, such as analogue equipment and synthesizers; the current tendencies of what he calls the "˜age of the home studio'; the awareness of sonic perception, as opposed to the danger of visual distraction; questions of terminology in electronic music and the shift to the digital domain in studios; among other things. [note by editor].